Difficulties in Teaching English for Specific Purposes: Empirical Study at Vietnam Universities - Nguyễn, Thị Tố Hoa (Canadian Center of Science and Education, 2017)
In recent years, teaching English, especially English for specific purposes at Vietnam universities has receiveda lot of attention from students, teachers, and relevant authorities because of not high teaching effectiveness.This results in the fact that students after graduation do not meet English requirements of employers,so unemployment becomes more serious. This is an alarming situation because English is becoming the almost indispensable communication language of young people nowadays. This empirical study consists of a survey of teachers and students at universities in Hanoi by listing the factors related to teaching English for specific purposes. Then, we give some recommendations for improving effectiveness of teaching English for specific purposes so that students can meet the English requirements for their work and lives.